Dryopteris Lijianxiuii (Dryopteridaceae), a New Species From China - Li, Xiaojuan; Wang, Xiao; Liu, Wei (Bangladesh Journal of Botany, 2021)
Dryopteris lijianxiuii X. J. Li, a new species of Dryopteris Adans. from Shandong, China, is described and illustrated. It is closer to D. lacera (Thunb.) O. Kuntze for its morphological and palynological characters of LM and SEM studies but differs by a number of characters, such as, the leaves rectangular roundlanceolate, apex acuminate, and without narrow sharply; sori ornamented in the upper or middle part of 1-3 pairs of pinnaes at the base of the leaf, and densely covered with the upper and middle pinnaes back; spore perispore with tuberculiform-rugulate protrusions, and surfaces with melting ice and snow ornamentation. The sp. nov. is described with LM and SEM characters of spore and fronds, compared with that of D. lacera (Thunb.) O. Kuntze and provided with photographs. Bangladesh J. Bot. 50(3): 747-753, 2021 (September) Special